Maternal direct additive effects and heterosis on the prolificacy features of rabbits at birth - Garc?a, Yoleisy; Ponce de Le?n, Raquel; Guzm?n, Gladys Sonia (Cuban Journal of Agricultural Science, 2013)
6 293 records of three diallelic crossings among four rabbit breeds (California, C; Chinchilla, CH; New Zealand, N and Semigiant, S) were used to determine the individual heterosis (hI), maternal (gM) and direct (gI) additive effects on the prolific features at birth: total born (TB), born alive (BA) and viability at birth (VIAB). A mixed generalized linear model was used with the help of macro GLIMMIX from SAS for estimating the average of each genetic group. The model considered, as fixed effects, the genetic group and the experiment as well as the random effect of the parturition order. The estimations were made through the linear contrast among the average obtained for each genetic group, according to the model of Dickerson. Differences among the genetic groups showed the advantages of the pure N for each features. The maternal additive effects were more important for these features than the direct. The litters of N breed benefit in the TB, while for the VIAB the young rabbit benefit with C genes. The maternal effects were favorable for the CH and N breeds, as maternal breeds for these indicators. A significant heterosis was found for the TB and BA between - 4.6 y - 6.5% for F1 CN and CHN crossing. The differences between the evaluated crossbreeding for these features can be attributed to the maternal and direct additive effect, favorable for using the N and C breeds as paternal and the CH and N as maternal breeds. Key words: rabbits, genetic parameters, crossing, prolificacy